Study of The Tafsir of Legal Verses on The Ethics of Debt and Pawn in Surah Al-Baqarah Verses 282–283 - Akhmad Rusdi; Mohammad Sahli Ali; Norsaleha Mohd Salleh (PT. Global Pustaka Ilmiah, 2025)
This study aims to examine in depth the legal content and ethical values contained in Surah Al-Baqarah verses 282–283, which relate to the practice of debt and pawn (rahn). This research focuses on understanding the legal verses (ayat al-ahkam) concerning the principles of justice, honesty, trustworthiness, and social responsibility in financial transactions (muamalah). The research method used is qualitative, employing a library research approach. The main data sources are derived from the Qur’anic text, particularly Surah Al-Baqarah verses 282–283, as well as classical and contemporary tafsir books such as Tafsir Ibn Kathir, Al-Qurtubi, Al-Maraghi, As-Sya‘rawi, and Al-Misbah by M. Quraish Shihab. The results show that verse 282 emphasizes the importance of documentation and witnesses in debt transactions to maintain justice and prevent disputes, while verse 283 provides provisions regarding pawn as a guarantee of trust when transactions are conducted without witnesses or written records. The ethical principles contained in these two verses honesty, trustworthiness, and responsibility form the foundation for the establishment of a just and civilized Islamic economic system. Thus, this study asserts that the legal values in the Qur’an have strong relevance to modern economic practices, particularly in building a financial system based on trust and social justice.